Lessons, discoveries, challenges, and results in an interdisciplinary learning community of higher education teachers - Sanches, Tatiana (2022)
The present study describes how a group of higher education teachers, from different disciplinary areas, came to constitute themselves as a learning community. Learning communities allow the exchange of information, tools, experiences, innovative practices, as well as knowledge transfer between colleagues in a faster and more relevant way. Despite the disciplinary diversity, the focus on university pedagogy grounded new practices. Teachers learned lessons through peer observation, discovered skills and competencies in the joint discussion, and accepted challenges to witness their experiences in professional forums foreign to their previous experience. It should be noted that the collaborative learning experience factor, which counts on another teacher as a reflective pair, allowed progressive social learning in this learning community that is ongoing for two years.